Expression of VEGF and CD-31 in traumatic ulcer of diabetic Wistar rats after application of Citrus limon peel essential oil - Nurina Febriyanti Ayuningtyas; Hening Tuti Hendarti; Bagus Soebadi; Meircurius Dwi Condro Surboyo; Priyo Hadi; Raziv Ganesha; Diah Savitri Ernawati; Riyan Iman Marsetyo (Elsevier, 2023)
Objective: Diabetes mellitus (DM) is a metabolic disease that delays the healing process, including the interruption of the processes of angiogenesis and vasculogenesis. The etiology of most angiogenic-related diseases, such as diabetes complications, includes the presence of hypoxia caused by declined vascular endothelium growth factor (VEGF) and CD-31. d-limonene, one of the main constituents of Citrus limon, is considered to have angiogenic, antioxidant, hypoglycemic, and anti-inflammatory activities. However, the exact mechanism of this process remains unclear. This study aimed to determine the potential of C. limon as a medication for diabetic ulceration. Methods: A total of 30 Wistar rats (Rattus novergicus) induced with DM and traumatic ulcers on the lower lip mucosa were divided into six groups-three each for control and treatment groups. Control groups were treated with CMC 5% gel, and treatment groups were administered with C. limon peel essential oil gel. The expression of VEGF and CD-31 was observed on days 5, 7, and 9. Immunohistochemical examinations were performed with the monoclonal antibodies anti-VEGF and anti-CD-31. ANOVA was conducted to analyze the differences between the groups (p < 0.05). Result: An increase in VEGF and CD-31 expression in the treatment group was observed compared with that of the control group (p < 0.05). Conclusion: Citrus limon peel essential oil gel increased VEGF and CD-31 expression during the healing process of traumatic ulcers in diabetes-afflicted Wistar rats.